Comportamento cardiorrespiratório durante o exercício em adolescentes obesos - Silva, Leslie Virmondes da (2017)
Introduction. In Brazil, 23% of adolescents aged 13 to 17 years are overweight, and 8% are obese. Obese children and adolescents will potentially be obese adults with a higher chance of developing cardiometabolic diseases. Cardiorespiratory behavior during the cardiopulmonary exercise test (CPT) provides a wealth of information about cardiovascular health. Objective. To test the hypothesis that apparently healthy obese adolescents present decreased functional capacity at maximal (VO2 peak) and submaximal loads (VO2 at 50% of the total time of the test and Oxygen Uptake Efficiency Slope, OUES) and impaired heart rate responses (HR) and systolic (SBP) and diastolic (DBP) blood pressure during exercise and ECP recovery. Methods. 18 obese adolescents (AO; +2 WHO Z-Score, 14.2 ± 0.3 years, 98.0 ± 4.6 kg) from 12 to 17 years old, pubertal, sedentary, who were not Dietary or drug treatment, compared to 11 eutrophic adolescents (EA, 14.9 ± 0.9 years, 55.0 ± 3.2 kg) matched by sex. Clinical BP, metabolic profile and cardiorespiratory behavior were evaluated during CPET. Results. The AO group had greater abdominal circumference and a greater amount and proportion of body fat than the AE group. In addition, AO had higher SBP and DBP and higher triglyceride and LDL-C levels and lower HDL-c levels than AE. In the TECP, the AO group had lower values than AE in the peak VO2 (24.8 ± 1.3 vs. 30.3 ± 2.8 ml / kg / min, P = 0.05) and in the% of the peak VO2 reached In relation to predicted VO2 (56.4 ± 3.5 vs. 70.3 ± 4.9%, P = 0.04). There was no difference in OUES between the groups. During the CPT there were differences in HR only at 50% of peak VO2, where the AO group had higher HR compared to AE (143 ± 4.2 vs. 129 ± 5.4 bpm, P = 0.04). In the AO group, higher SBP values were found at rest, peak, 1st, 2nd and 6th min of recovery, whereas DBP was only higher in the 2nd and 4th minutes of recovery compared to the AE group. In addition, there was a tendency for greater minute ventilation (VEpico) at the peak of effort in the AO (78.1 ± 4.1 vs. 63.3 ± 5.6 L / min, P = 0.06) and there was no difference in VE To 50% of the peak VO2 (26.3 ± 1.6 vs. 22.7 ± 3.1 L / min, P = 0.374). There was no difference between the groups in the maximum respiratory quotient (QR) and maximum HR. Regarding physical performance, the OA group presented lower total exercise time (8.0 ± 0.3 vs. 9.3 ± 0.8 min, P = 0.04), lower speed (7.3 ± 0.1 P = 0.05) and lower slope at peak exercise (6.2 ± 0.5 vs. 8.4 ± 1.1%, P = 0.03 ) Compared to EC. Conclusion. Adolescent obesity triggers metabolic alterations, favoring the onset of the metabolic syndrome. Among these changes, it is worth noting the increase in blood pressure responses at the peak of exercise and a lower decrease in systolic and diastolic blood pressure in the post-exertion recovery, thus suggesting a possible dysfunction in the sympatho-vagal balance.